Faktor-Faktor yang Berhubungan dengan Kejadian Stunting pada Balita - Anna Virjunesty Lehan; Tuti Asrianti Utami; Paramitha Wirdani Ningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the factors associated with the incidence of stunting in toddlers at the Oemasi Health Center. This research uses a quantitative method with a correlative descriptive design using a cross-sectional approach. The results showed that there was a significant relationship between the mother's attitude (p-value = 0.001), family income (p-value = 0.000), history of exclusive breastfeeding (p-value = 0.001), and history of complementary feeding (p-value = 0.001) with the incidence of stunting in toddlers. In conclusion, the mother's attitude, exclusive breastfeeding, provision of timely and appropriate quality complementary feeding (MPASI), and family income are related to the incidence of stunting in toddlers at the Oemasi Health Center in Kupang district. Keywords: Exclusive Breastfeeding, Complementary Breastfeeding, Family Income, Mother's Attitude, Stunting